Silver-and-Sulphur-Codoped Fe3O4/TiO2 as a Magnetically Separable Photocatalyst for Methylene Blue Degradation under Visible Light - Kunarti, Eko Sri; Agustiningsih, Dewi; Pambudi, Fajar Inggit; Rusli, Stefen; Rusdiarso, Bambang (Molekul, 2024)
This research aimed to investigate how the addition of silver and sulphur dopants modified the TiO2 photocatalyst to enhance its responsiveness to visible light and improve its photocatalytic activity for methylene blue degradation. In addition, Fe3O4 was also added as a core to add magnetic properties to the photocatalyst material. The Fe3O4/TiO2-Ag/S materials were prepared using FeCl3.6H2O and FeSO4.7H2O as the magnetite precursors, titanium tetraisopropoxide (TTIP) as the TiO2 precursor, while AgNO3 and CH4N2S were used as the sources for silver and sulphur dopants, respectively. The synthesized materials were next characterized using FT-IR, XRD, UV-Vis spectrophotometer, SEM-EDX, TEM, and VSM. The activity of the photocatalyst was then assessed through methylene blue degradation in a closed reactor involving various contained Ag:S ratios and reusability examination. The evaluation of photocatalytic degradation results was performed using UV-Vis spectrophotometry. Afterwards, the research findings indicate that the Fe3O4/TiO2-Ag/S was successfully synthesized and exhibited magnetic properties with a saturation magnetization value of 5.33 emu/g. The highest photocatalytic activity (98.21%) was observed in Fe3O4/TiO2-Ag/S (1:1) with a band gap energy value of 2.64 eV under visible light exposure at pH 10, 120 min, 10 mg mass of the photocatalyst, and methylene blue concentration of 5 mgL-1. Furthermore, the Fe3O4/TiO2-Ag/S photocatalyst was known to perform good stability through four reuse cycles.